On the influencing mechanism of unsafe behaviour of coal miners based on hierarchical regression. (2017) - Li, Hong-xia; Di, Hong-xi
To study the relationship between the job stress and unsafe behaviour of coal miners, reduce the unsafe behaviour of coal miners triggered by their job burnout, and effectively improve job performance of coal enterprises, empirical research was made to explore the impact of job stress on the unsafe behaviour of coal miners and mediating effect of job burnout on the relationship between the job stress and unsafe behaviour of coal miners. A total of 194 valid samples were collected and analysed to draw following conclusions. Job stress and unsafe behaviour of coal miners have a significantly positive correlation; job stress has mediating effect on the relationship between the job stress and unsafe behaviour of coal miners. Moreover, coal enterprises are recommended to take measures, such as conducting stress management, timely intervening in fatigue operation, providing more promotion channels and so on, to alleviate job stress of coal miners, in order to effectively prevent and control unsafe behaviours of coal miners.